Diagnostic characteristics and management outcome in patients with acromegaly: a 15-year experience at a tertiary care hospital in Pakistan - Shehla Tabassum; Sajjad Ali khan; Nanik Ram; Najmul Islam (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the diagnostic features of acromegaly, and analyse its management outcomes over a 15-year period in a tertiary care setting. Method: The descriptive, cohort, retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised data of adult patients of either gender diagnosed with acromegaly based on biochemical and radiological evidence between January 2005 and December 2019. Data was retrieved from the medical records. Data was analysed using SPSS 19. Results: Of the 84 subjects, 54(64.3%) were males and 30(35.7%) were female. The overall mean age was 38.69±13.52 years. The patients presented 5.43±4.3 years after the onset of symptoms, with somatic growth features, such as enlarged hands and feet which was the most common complaint 81(96.4%). Of all the patients, 73(86.9%) underwent trans-sphenoidal surgery for the removal of the pituitary adenoma, while 11(13.1%) opted out of the surgical option. Further, 9(12.3%) patients showed biochemical and radiological remission 6 months post-surgery. Out of the remaining 64(87.7%) patients, 38(59.4%) received radiosurgery or radiotherapy, 15(23.4%) underwent repeat trans-sphenoidal surgery, and 11(17.2%) chose medical treatment. Conclusion: Majority of patients failed to achieve remission after trans-sphenoidal surgery, which is the first line of treatment. Radiotherapy/repeat surgery was generally the options taken by those with persistent disease. Key Words: Acromegaly, Characteristics, Diagnosis, Management, Outcome, Pituitary tumour, Growth hormone.